PERSPECTIVES ON PROFESSIONAL PERFORMANCE GROWTH IN THE FIELD OF ECONOMICS IN THE HIGHER EDUCATION INSTITUTIONS - Loredana HOBEANU VĂCĂRESCU (Management & Marketing)
The training and improvement of the members’ performances from the academic community represent only a part of their continuous perfecting process made in accordance with the latest legislation. As a conventional formulation states, the faculty’s performance and success are given by all its results and behaviors and it is by these means that individual and group contributions are measured. High standard performances determine precise local, national or European programs meant either to increase professional development or stimulate the resources and professional opportunities provided by the academic environment .In order to have a well-rated performance, the entire staff of the university should be aware of their involvement and responsible for the achievement of the tasks, objectives and mission of the university.